PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA KANTOR PUSAT UNIVERSITAS TERBUKA PONDOK CABE - Ussalam, Abror; Darwinsyah, Muhammad (Taksasila Edukasi Insani, 2024)
This research aims to test and analyze the influence of Leadership Style and Organizational Culture on employee performance at the Pondok Cabe Open University Head Office.This research design is quantitative with an associative type. This research uses primary data. The population used was 81 employees of the Pondok Cabe Open University Head Office. This research method used is a quantitative method that is associative with a sampling technique, namely a saturated sample. The data analysis technique used was multiple linear analysis using SPSS version 2.0.The results of this research show that leadership style has a positive and significant effect on employee performance at Pondok Cabe Open University. Organizational culture has a positive and significant effect on employee performance at Pondok Cabe Open University. Leadership Style and Organizational Culture have a positive relationship and have a significant effect on Employee Performance at Pondok Cabe Open University.